A Woman's conflict : the special relationship between women and food - Jane Rachel Kaplan (Englewood Cliffs, NJ : Prentice-Hall, 1980)
A Spectrum book
Includes bibliographies and index
Keywords: Women -- Nutrition -- Psychological aspects; Women -- Nutrition -- Social aspects; Body image; Food habits